2013
DOI: 10.1016/j.drugalcdep.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cannabis use disorders: Results from the National Epidemiologic Survey of Alcohol and Related Conditions

Abstract: Background To examine gender differences among individuals diagnosed with DSM-IV lifetime cannabis use disorder (CUD). Methods A nationally representative sample of U.S. adults aged 18 years or older that were diagnosed with lifetime CUD (N= 3,297): Men (N = 2,080), Women (N = 1,217). Data were drawn from the 2001–2002 National Epidemiologic Survey on Alcohol and Related Conditions (NESARC, n = 43,093). The survey response rate was 81%. Results Nearly all individuals with CUD had a psychiatric comorbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
178
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(197 citation statements)
references
References 84 publications
12
178
2
Order By: Relevance
“…The fact that the sample was mostly male is not uncommon for a cannabis using population (Copeland & Swift, 2009;Khan et al, 2013); and while the construct of ethnicity is often ill-defined, including in the present study, the fact the majority of the sample self-identified as Caucasian is representative of the population of Calgary, AB (Statistics Canada, 2011). Only one demographic difference emerged among the different recovery pathways.…”
Section: Sample Characteristicsmentioning
confidence: 78%
“…The fact that the sample was mostly male is not uncommon for a cannabis using population (Copeland & Swift, 2009;Khan et al, 2013); and while the construct of ethnicity is often ill-defined, including in the present study, the fact the majority of the sample self-identified as Caucasian is representative of the population of Calgary, AB (Statistics Canada, 2011). Only one demographic difference emerged among the different recovery pathways.…”
Section: Sample Characteristicsmentioning
confidence: 78%
“…Further, male CA were more likely diagnosed with any psychiatric disorder, any substance use disorder and antisocial personality disorder compared with female CA, whereas female CA had more mood, anxiety, and externalizing disorders (Khan et al, 2013). Male CA also had longer episodes of abuse, smoked more joints, and were older at remission than female CA (Khan et al, 2013). Nevertheless, it has to be noted that some of these gender differences might reflect social and cultural factors influencing exposure and responses to cannabis rather than biological differences in the sensitivity to cannabis.…”
Section: Group By Gender Interactions On Baseline and Mp-induced Chanmentioning
confidence: 94%
“…That is, smoking cannabis was associated with decreased quality of life, particularly in female CA (Lev-Ran et al, 2012). Further, male CA were more likely diagnosed with any psychiatric disorder, any substance use disorder and antisocial personality disorder compared with female CA, whereas female CA had more mood, anxiety, and externalizing disorders (Khan et al, 2013). Male CA also had longer episodes of abuse, smoked more joints, and were older at remission than female CA (Khan et al, 2013).…”
Section: Group By Gender Interactions On Baseline and Mp-induced Chanmentioning
confidence: 99%
“…Despite many individuals meeting the criteria for cannabis dependence, few seek formal treatment (Vendetii et al, 2002). A nationally representative study (N= 49,093) found that only 13% of cannabisdependent individuals sought formal treatment over the course of their lifetime (Khan et al, 2013). In comparison, approximately 13% of alcohol dependent individuals entered treatment in a given year (Teesson et al, 2006).…”
Section: Introductionmentioning
confidence: 99%